Towards Standardization of Forensic Services across the Commonwealth of Independent States - A. I. Usov; S. A. Kuz’min (Теория и практика судебной экспертизы, 2016)
The paper outlines the role of such innovations as standardization and quality assurance in forensic operations conducted on the territory of the Commonwealth of Independent States (CIS). Rationales are provided for pathways towards standardization of forensic practice as a means of improving the efficiency of forensic contribution to the due process of law by resolving issues that require special knowledge. The authors examine different approaches to the understanding of quality in forensic practice and offer a definition that reflects the hierarchically structured system of law enforcement and courts' forensic needs.